2021
DOI: 10.1002/mnfr.202000425
|View full text |Cite
|
Sign up to set email alerts
|

The Human Milk Oligosaccharides 3‐FL, Lacto‐N‐Neotetraose, and LDFT Attenuate Tumor Necrosis Factor‐α Induced Inflammation in Fetal Intestinal Epithelial Cells In Vitro through Shedding or Interacting with Tumor Necrosis Factor Receptor 1

Abstract: Scope Human milk oligosaccharides (hMOs) can attenuate inflammation by modulating intestinal epithelial cells, but the mechanisms of action are not well‐understood. Here, the effects of hMOs on tumor necrosis factor‐α (TNF‐α) induced inflammatory events in gut epithelial cells are studied. Methods and results The modulatory effects of 2’‐fucosyllactose, 3‐fucosyllactose (3‐FL), 6’‐sialyllactose, lacto‐N‐tetraose, lacto‐N‐neotetraose (LNnT), lactodifucotetraose (LDFT), and lacto‐N‐triaose (LNT2) on immature (FH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…For example, 2’-FL promoted cell differentiation 36 and inhibited inflammatory responses by suppressing the expression of CD4, a member of the LPS-receptor complex, thus decreasing LPS-induced inflammatory responses 18 and attenuating TNF-induced inflammation. 37 This evidence from immature intestinal epithelial cells supports the potential function of 2’-FL in direct promotion of intestinal development and the maturation of the immune system in the early stage of life. This study identified a previously unrecognized direct effect of 2’-FL on the inhibition of 5-FU–induced apoptosis in normal mature IECs.…”
Section: Discussionmentioning
confidence: 52%
“…For example, 2’-FL promoted cell differentiation 36 and inhibited inflammatory responses by suppressing the expression of CD4, a member of the LPS-receptor complex, thus decreasing LPS-induced inflammatory responses 18 and attenuating TNF-induced inflammation. 37 This evidence from immature intestinal epithelial cells supports the potential function of 2’-FL in direct promotion of intestinal development and the maturation of the immune system in the early stage of life. This study identified a previously unrecognized direct effect of 2’-FL on the inhibition of 5-FU–induced apoptosis in normal mature IECs.…”
Section: Discussionmentioning
confidence: 52%
“…HMOs are reported to exert a number of protective effects in the intestinal tract, including the stimulation of the growth of commensal bacteria [ 24 , 25 ], inhibition of the growth of enteric pathogens and elaborated toxins [ 13 , 26 ], promotion of goblet cell-derived mucin production and secretion [ 27 ], modulation of both innate and adaptive immunity [ 28 ] and maintenance of the integrity of the epithelial cell barrier [ 17 , 19 ]. Traditionally, the structure and specificity of responses of HMOs are associated with effects on microbial functions related to their role either as prebiotics or anti-adhesive molecules [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, 2′-fucosyllactose quenches host inflammatory response through the specific inhibition of Toll-like receptor 4 and the alteration of CD-14 expression [ 38 , 49 ] and NFκB [ 40 ]. On the other hand, 3-fucosyllactose, lacto-N-neotetraose and lactodifucotetraose reduce inflammation by blocking the activation of TNF-α [ 28 ]. Sialyated HMOs have been described to increase host susceptibility to colitis [ 50 ] and improve cognitive function in vivo [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Here, the LDFT concentrations were statistically significantly different between the time points 8–15 days and 3 months, 8–15 days and 4 months, as well as 8–15 days and 6 months ( q < 0.05, mixed-effects model (one-way) for repeated measures). LDFT is positively correlated with other α-1,2-fucosylated HMOs, 2′-FL, LNFP-I, lacto-N-difucohexaose-I (LNDFH-I), difucosyllacto-N-hexaose a (DFLNHa) [ 14 ], and it has been reported to significantly attenuate TNF-α induced inflammation in immature intestinal epithelial cells in vitro [ 46 ]. A similar effect has also been detected with 3-FL and LNnT [ 46 ].…”
Section: Discussionmentioning
confidence: 99%